WMO operations manual for sampling and analysis techniques for chemical constituents in air and precipitation - World Meteorological Organization (WMO / World Climate Programme Department ; 299, 1974)
Part I - The minimum programme at regional air-pollution stations Part II - Guidelines for baseline stations and regional stations with extended programmes